EUTHANASIA REVIEW FROM APPLICABLE CRIMINAL LAW IN INDONESIA (Case Study Medan District Court) - Mega; Nelvitia Purba (SEAN Institute, 2022)
Apart from technological advances that have many positive effects, it's just that for some people think that these advances have negative effects as well. The negative influence in question is the human thought of a death. The negative influence of technological advances in health science causes the family of a patient or the patient himself to apply to medical personnel or doctors to hasten the death of a patient in order to relieve pain so that the patient can rest in peace and this is what we call euthanasia. In line with the title of this research, namely